Comparative Study on Rheological Properties of Wheat Flour Types for Industrial Usage - Ramzan, Saniya; Sharif, Mian Kamran (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2023)
Wheat, Triticum aestivum is one of the grains consumed worldwide as a staple food used in a variety of processed commodities. The rheological properties of the raw commodity will define the end product’s characteristics, whether it is of high quality or not. Moreover, the processes of, e.g., grinding, crushing, etc., of grain will also determine the flour’s content, which will further go on for other processes and be delivered to the consumer in the end product. To that end, the properties and effects of different wheat flour contents were analyzed for different types of flour 550, 1050 and whole grain flour available in Germany. These samples were analyzed to select the best-suited commodity for industrial purposes. Falling number, gluten percentage, starch content, viscosity and farinograph were determined for flour during baking test and bread volume for its products. Three types of flour with different content percentages were tested for comparison to find the best-suited type for the baking purpose among them. Among the types 550, 1050 and whole grain flour, the parameters are fitter for bread baking process is 550 type as the results show falling number = 450.25; 334; 296.87; starch (%) = 75.45; 69.72; 64.75; gluten (%) = 38.65; 31.84 and 21.44, and bread volume is 400, 340 and 300 ml respectively. This study suggested that flour with more starch content and a falling number will produce a reasonable volume and more appealing bread regarding sensory attributes.